Politics and history in band societies - Leacock, Eleanor Burke 1922-; Lee, Richard B. (Cambridge University Press, 1982)
Collection of papers giving new information on the history and culture of contemporary gathering and hunting peoples from Canada, India, Africa, Australia and the Philippines. Focuses on two themes: 1) the techniques which band-living foraging peoples employ to organize their social and economic lives, and 2) their current fight for the right to their own lands and for a measure of cultural and political autonomy.